Endocrine and psychological aspects of sexual dysfunction in Klinefelter patients. - Ferlin, A; Selice, R; Angelini, S; Di Grazia, M; Caretta, N; Cavalieri, F; Di Mambro, A; Foresta, C (Andrology, 2018)
Klinefelter syndrome is a frequent cause of hypogonadism, but despite hundreds of publications on different aspects of Klinefelter syndrome, only a few studies dealt with sexual dysfunction. In particular, testosterone is critical for various aspects of sexual response, but its role on sexuality in Klinefelter syndrome patients is debatable and no studies have evaluated the efficacy of testosterone treatment on sexual dysfunction in these subjects. Furthermore, the impact of psychological and relational aspects on sexual function of Klinefelter syndrome subjects is poorly defined. In this study, we aimed to determine the presence and type of sexual dysfunctions in Klinefelter syndrome subjects; to correlate them with testosterone levels and psychosexological and relational domains; and to evaluate the effects of testosterone therapy. We studied 62 non-mosaic naïve Klinefelter syndrome patients and 60 age-matched controls by means of medical history, psychosexological history, 15-item International Index of Erectile Function questionnaire, endocrine assessment, and dynamic penile color Doppler ultrasound. Twenty-five hypogonadal Klinefelter syndrome patients were studied after 6 months of testosterone replacement therapy. Klinefelter syndrome subjects have reduced 15-item International Index of Erectile Function scores regarding sexual desire, intercourse satisfaction, and overall satisfaction with respect to controls, and these aspects were significantly associated with testosterone levels. Klinefelter syndrome subjects had also higher prevalence of erectile dysfunction, but no relation with testosterone levels was evident. A high prevalence of a range of psychological disturbances was present in Klinefelter syndrome subjects with erectile dysfunction with respect to those without erectile dysfunction. No statistical difference in the prevalence of premature and delayed ejaculation was observed between Klinefelter syndrome and control subjects. Testosterone replacement therapy improved sexual desire, intercourse satisfaction, and overall satisfaction scores, but had no effect on erectile function. Penile color Doppler ultrasound was normal in all subjects. This study shows that sexual dysfunction in Klinefelter syndrome is multifactorial and related only in part to hypogonadism and largely to psychological disturbances. Evaluation and therapy of sexual dysfunction should include a combined andrological and psychosexological approach.